Efek Teripang Terung (Phyllophorus Sp.) Terhadap Kadar HDL Dan LDL Tikus Dengan Diet Tinggi Lemak - ANAK AGUNG ISTRI AGUNG, SRILA NATASWARI; LESTARI DEWI; SOEDARSONO; INDRI NGESTI RAHAYU (Hang Tuah Medical Journal, 2025)
Cholesterol is divided into two different forms, including HDL (high-density lipoprotein, also referred to as "good fat". LDL (low-density lipoprotein), sometimes known as "bad fat". A buildup of cholesterol levels in the blood that can lead to cardiovascular disease. Sea cucumbers contain flavonoids which are a class of phenolic compounds. Flavonoids have properties as antioxidants. This study was conducted to determine the effect of ethanol extract of sea cucumber (Phyllophorus sp.) on HDL and LDL levels in wistar strain white rats induced by high fat diet. This study was conducted in the biochemistry laboratory of the Faculty of Medicine, Hang Tuah University using 30 white rats (Rattus norvegicus) male wistar strain. The rats were divided into 5 groups, namely, groups of animals that did not receive treatment, groups of animals fed a high-fat diet, groups of animals fed a high-fat diet and sea cucumber ethanol extract 8.5mg/kgBB, groups of animals fed a high-fat diet and sea cucumber ethanol extract at a dose of 17mg/kgBB, groups of animals fed a high-fat diet and simvastatin. On the 35th day, HDL and LDL levels were examined in all groups. The conclusion of the results of this study is that the administration of sea cucumber ethanol extract can increase HDL levels even though it is not significant, and can significantly reduce LDL levels. Keywords: Sea cucumber ethanol extract (Phyllophorus sp.), HDL, LDL, Wistar white rat, high fat diet